2008
DOI: 10.2337/db07-0847
|View full text |Cite|
|
Sign up to set email alerts
|

Transcription Factor 7-Like 2 Regulates β-Cell Survival and Function in Human Pancreatic Islets

Abstract: OBJECTIVE-Type 2 diabetes is characterized by impaired insulin secretion in response to increased metabolic demand. This defect in ␤-cell compensation seems to result from the interplay between environmental factors and genetic predisposition. Genome-wide association studies reveal that common variants in transcription factor 7-like 2 (TCF7L2) are associated with increased risk of type 2 diabetes. The aim of the present study was to establish whether TCF7L2 plays a role in ␤-cell function and/or survival. RESE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
242
4
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(264 citation statements)
references
References 43 publications
11
242
4
7
Order By: Relevance
“…Reducing TCF7L2 protein production using siRNA led to a small reduction in glucose-induced insulin secretion and a much greater reduction in GLP1-induced secretion [12,13]. In the first study [12], knockdown of TCF7L2 in human islets decreased beta cell proliferation, and overexpression of TCF7L2 had a protective effect against glucose-and cytokine-induced apoptosis, suggesting a role in regulation of beta cell mass. However, the second study points to a functional defect [11].…”
Section: Tcf7l2 Incretins and The Beta Cellmentioning
confidence: 97%
See 2 more Smart Citations
“…Reducing TCF7L2 protein production using siRNA led to a small reduction in glucose-induced insulin secretion and a much greater reduction in GLP1-induced secretion [12,13]. In the first study [12], knockdown of TCF7L2 in human islets decreased beta cell proliferation, and overexpression of TCF7L2 had a protective effect against glucose-and cytokine-induced apoptosis, suggesting a role in regulation of beta cell mass. However, the second study points to a functional defect [11].…”
Section: Tcf7l2 Incretins and The Beta Cellmentioning
confidence: 97%
“…• Decreased beta cell mass Decreased beta cell proliferation following TCF7L2 knockdown [12] Decreased 'maximal' insulin secretion-response to arginine at 28 mmol/l glucose [10] • Impaired insulin processing or release Altered SLC30A8, Munc18-1 and Stx1A expression in mice with Tcf7l2 knockdown [13] Increased proinsulin:insulin ratio in rs7903146 T allele carriers [9,17] Decreased 'maximal' insulin secretion-response to arginine at 28 mmol/l glucose [10] • Impaired GLP1 signalling in beta cells [9,11] Response to GLP1 impaired to greater extent than that to i.v. glucose [10] • Decreased glucagon secretion reducing beta cell insulin secretion [9] Needs replicating…”
Section: Mechanisms Whereby Altered Tcf7l2 Production or Function Maymentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent studies implicated β-cell dysfunction as the underlying cause of diabetes in patients with the TCF7L2 risk variant [2][3][4][5] and have suggested that Wnt signalling plays an important role in both pancreatic development and in the function of mature pancreatic islets [6]. The activation of the canonical Wnt pathway, by ligands such as Wnt3a, has been of particular interest as it can increase β-cell proliferation, decrease apoptosis and improve glucose stimulated insulin secretion [6][7][8][9][10][11][12]. However there is now increasing evidence that non-canonical Wnt ligands such as Wnt4 can antagonise the signalling mediated by Wnt3a and may play an equally important role in β-cell function [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In line with this, molecular studies indicate co-activation of the gene encoding glucokinase-a major regulator of glucose-sensing in beta-cells-by β-catenin [3]. In addition, knocking down the gene encoding TCF7L2 in adult murine and human islets in vitro reduces beta cell proliferation and insulin secretion [7], emphasising the importance of this transcription factor for beta cell function. Of note, TCF7L2 is a classic target for β-catenin.…”
Section: Frpmentioning
confidence: 80%